A low-cost in-line ozone gas monitor via ultraviolet absorption spectroscopy - Al-Sabbagh, Baseem H.; Al-Alawy, Ahmed Faiq; Almalichy, Abdulameer (Iraqi Journal of Chemical and Petroleum Engineering, 2025)
A low-cost in-line ozone monitor based on the principle of ultraviolet absorption was built and tested for different ozone for concentrations up to 300 mg h-1 and flow rates up to 5 lpm using air as a feed source. A widely available T5 ultraviolet (UV) tube was used as a UV source and two UV light absorption cells were made to act as reference and measuring cells. The output of the two cells was used to calculate the ozone concentration using Beer-Lambert’s law. To correlate the output readings of the ozone monitor with those obtained using the iodometric titration method, a correction factor of 1.5117 was determined and applied. The results demonstrate a strong linear correlation ≥0.99 between estimated and measured ozone concentration values. Relative errors less than 10% were observed for ozone concentrations ranging from 400 to 5000 ppb, while a relative error up to 16% was reported for concentrations below 400 ppb. The developed monitor offers a cost-effective alternative to expensive ozone monitoring systems for standard applications, with a total construction cost under 100.